2015
DOI: 10.3389/fpsyg.2015.00895
|View full text |Cite
|
Sign up to set email alerts
|

The development of the effect of peer monitoring on generosity differs among elementary school-age boys and girls

Abstract: The purpose of this study was to examine the effect of peer monitoring on generosity in boys and girls aged 6–12 years. A total of 120 elementary school students played a one-shot dictator game (DG) with and without peer monitoring by classmates. Children decided how to divide 10 chocolates between themselves and a classmate either in a condition in which their allocations were visible to their peers, or in private. While the effect of peer monitoring on the allocation amount in the DG was clearly present in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…An early study found larger audience effects in 8 year olds compared to 4 year olds performing a balance task (Maccracken and Stadulis 1985). In a dictator game applied to children from 6 to 12 years of age, only children above age 9 were influenced by peer observation of their behaviour (Takagishi et al 2015). Electrophysiological measures also change with age: ERN recorded from children performing a motor task was larger when an audience was present, but this effect was even larger in older children (9–11 years) compared to younger children (7–8 years).…”
Section: Diversity Of the Participantsmentioning
confidence: 99%
“…An early study found larger audience effects in 8 year olds compared to 4 year olds performing a balance task (Maccracken and Stadulis 1985). In a dictator game applied to children from 6 to 12 years of age, only children above age 9 were influenced by peer observation of their behaviour (Takagishi et al 2015). Electrophysiological measures also change with age: ERN recorded from children performing a motor task was larger when an audience was present, but this effect was even larger in older children (9–11 years) compared to younger children (7–8 years).…”
Section: Diversity Of the Participantsmentioning
confidence: 99%
“…The internalization of social norms and anticipated responses by others further develops throughout elementary school, as shown by the finding that DG giving increases first if the player's choice is observed by other players, followed by a gradual increase in the situations where the player's choice is anonymous (54). Generally, children's giving in the DG increases as they age (54)(55)(56). Consequently, default giving in the DG increases and the pattern shifts from that in Fig.…”
Section: Discussionmentioning
confidence: 90%
“…By the age of 5, children start internalizing others' responses and give more in the DG when they are monitored by the experimenter than when they are not (53). The internalization of social norms and anticipated responses by others further develops throughout elementary school, as shown by the finding that DG giving increases first if the player's choice is observed by other players, followed by a gradual increase in the situations where the player's choice is anonymous (54). Generally, children's giving in the DG increases as they age (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that 5‐year‐old children were more generous when the recipient could see their sharing behavior than when the recipient could not (Leimgruber, Shaw, Santos, & Olson, ). Similarly, children were more generous when someone was sitting nearby than when they were alone (Engelmann, Herrmann, & Tomasello, ; Engelmann, Over, Herrmann, & Tomasello, ; Takagishi et al, ). Furthermore, the presence of a live experimenter during social interactions increased 5‐year‐old children's generosity whereas the mere presence of an image of eyes did not (Fujii, Takagishi, Koizumi, & Okada, ; Vogt, Efferson, Berger, & Fehr, ).…”
Section: Introductionmentioning
confidence: 99%